COMPLEX APPROACH FOR PORTABLE CRYOPRESERVATION OF SEGMENTS OF BLOOD VESSELS WITH POLYDIMETHYLSILOXANE - S. E. Lauk-Dubitsky; T. A. Astrelina; A. A. Fedyunin; I. A. Burkov; E. M. Kildyushov; S. V. Lischuk; I. A. Novikov; A. V. Pushkarev; V. A. Brumberg; A. V. Shakurov; D. P. Samchuk; I. V. Kobzeva; et al. (Вестник трансплантологии и искусственных органов)
Aim. To develop a safe protocol for cryopreservation of segments of iliac arteries straight after their retrieval from post-mortem donor with the use of polydimethylsiloxane as a coolant and cryoprotectant.Materials and methods. Eleven segments of iliac arteries were retrieved from post-mortem donor and divided into four groups including control. Based on preliminary heat and cold transfer mathematical modeling and tests with tissueequivalent phantom arterial segments were placed on plastic mounts and cryopreserved by following protocol: groups 1 and 2 were immersed in polydimethylsiloxane and cooled rapidly at 180 °С/min to –75 °С. Group 3 segments were cryopreserved at 1,6 °С/min in PDMS – fi lled cryo-container placed in the freezer at –80 °С. All segments were defrosted by immersion in PDMS at +24 °С and then examined for morphology changes by histological methods and SEM. EDS analysis with the use of AzTech software also was performed for Si – content evaluation. Restricted biomechanical tests were conducted for group 2 segments.Results. There were no signifi cant morphological differences between segments of the control and cryopreserved groups except for the segment with slow cooling.Conclusion. Mobile cryopreservation may allow increasing the effi ciency of retrieval of a large number of donor tissues for possible later use in the processing of bioprostheses of blood vessels; or, after decellularization, as well as tissue-specifi c matrices for tissue-engineering blood vessels.